On an Effective Method of The Effect of Cavities, Inclusions and Crack Upon the Stress Fields in Elastic Media - Sokołowski, M. (Engineering Transactions, 1986)
Cracks, boles and inclusions introduce certain disturbances into the stress fields produced in elastic media by external loads. Theoretical foundations of the analysis of such stress fields are well known and, in principle, problems of this kind may always be reduced to the solution of the corresponding sets of integral equations. However, the effective determination of stresses may prove to be not so simple, first of all in the ceses when the number of defects is high and the stress fields are singular. In such cases the finite differences or finite elements methods become impractical. This paper is aimed at presenting such an approximate method of analysis. Which resembles the approach known from elementary structural mechanics and which. is applied to statically indeterminate structures; it reduces the problem considered to the solution of a rather simple set of algebraic equations. If the mutual distances between the elliptical inclusions and cavities are not smaller than their dimensions, the accuracy achieved will be satisfactory from the point of view of engineering applications.